2021
DOI: 10.28945/4879
|View full text |Cite
|
Sign up to set email alerts
|

Doctoral Students’ Learning Experiences in Ghana: Exploring a New Curriculum Using Bourdieu’s Concepts

Abstract: Aim/Purpose: To utilize Pierre Bourdieu’s (1984, 1986) concepts of capitals, habitus, and field to explore and critically analyze doctoral students’ learning experiences with a new doctoral curriculum introduced by a Ghanaian university. Background: Global competition and labor market reforms have ignited the need for higher education institutions to reimagine their doctoral programs, develop and align them with labor market demands and national priorities. Methodology: The research was conducted as a quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Common concerns were related to the observation that African universities have limited resources to mimic the doctoral supervision practices of higher-income countries. A suggestion for effective supervision was described as both the supervisor and the student meeting regularly to reflect on their relationship, responsibilities, project timelines and interests [ 17 , 25 , 26 ]. Supervisors are also expected to identify individual student needs so that individualised supervision models can be designed [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Common concerns were related to the observation that African universities have limited resources to mimic the doctoral supervision practices of higher-income countries. A suggestion for effective supervision was described as both the supervisor and the student meeting regularly to reflect on their relationship, responsibilities, project timelines and interests [ 17 , 25 , 26 ]. Supervisors are also expected to identify individual student needs so that individualised supervision models can be designed [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The first; Research done by (Salifu & Agbenyega, 2021) title "Doctoral Students' Learning Experiences In Ghana: Exploring New Curriculum Using Bourdieu's Concepts". Findings The research found that, although the participants were broadly satisfied with some aspects of their programs, the additional cost associated with its duration, the lack of quality and timely feedback from supervisors, and difficulty accessing conference funding were key challenges to achieving the ultimate goals of the new doctoral curriculum.…”
Section: Preliminary Research Studiesmentioning
confidence: 99%